OPÇÃO DE CARREIRA E AS ATITUDES EM RELAÇÃO À MATEMÁTICA DE ESTUDANTES INGRESSANTES NA UNIVERSIDADE: O CASO DA UFMS, CÂMPUS DE NAVIRAÍ - Lenita Regina de Oliveira Dreyer (2023)
This study refers to a master's research linked to the Postgraduate Program in Mathematics Education (PPGEduMat) at the Federal University of Mato Grosso do Sul (UFMS), research line "Teacher Training and Curriculum". The investigation aimed to analyze to what extent the attitudes towards Mathematics of incoming students in the courses of the Campus of Naviraí of the Federal University of Mato Grosso do Sul influenced their career choice. The theoretical framework included studies from the field of Psychology of Mathematics Education in relation with processes of career choice. Methodologically, the research was carried out using a mixed approach, with data produced through questionnaires and the "Attitudes Scale'' towards Mathematics formulated by Aiken and translated, adapted, and validated by Brito (1996). In summary, the analysis showed that the students' negative relationship with Mathematics influenced their career choice at the time of choosing a degree course, although for the surveyed population, this data is lower when compared to the perception of positive attitudes. The data also showed that students' experiences in Basic Education influenced the formation of attitudes (both positive and negative), requiring a movement of resignification so that students gain confidence to venture into any area of knowledge.